Epidemiology and control measures of an OXA-48-producing Enterobacteriaceae hospital outbreak. Issue 3 (September 2020) - Sivaramakrishnan, Anand; Mack, Damien; El-Mugamar, Husam; Jacques, Judy; Paget, Stephanie; Phee, Lynette; Carter, Yvonne
Summary: Carbapenemase-producing Enterobacteriaceae (CPE) are a significant challenge to healthcare and infection prevention and control teams. In the UK, OXA-48-like carbapenemases are frequently reported. We describe an outbreak of OXA-48-like producing Enterobacteriaceae and the control measures that proved effective in containing further spread. Aim: To describe epidemiologic and laboratory features of outbreak and highlight key control interventions. Findings: Following the introduction of an increased sensitivity CPE screening protocol, OXA-48-like CPE were identified in screening and clinical samples from 96 patients across five hospital wards between November 2017 and July 2018. Klebsiella pneumoniae and Enterobacter cloacae were the most frequently isolated organisms, although a range of OXA-48-like positive organisms were identified. The outbreak was contained utilising certain key interventions, including the modification of laboratory screening processes, engagement of hospital senior management, clear and frequent communication and a strong 'ward presence' by the infection prevention and control team (IPCT). Conclusion: Our report describes how a change in laboratory CPE screening process unmasked a CPE outbreak. The range of bacterial species harbouring the OXA-48-like mechanism suggested plasmid-mediated transfer of resistance. The timely implementation of interventions using a clinical, 'ward-based' approach to infection prevention and control highlights the importance of behavioural change in infection control interventions and enabled the termination of a large outbreak without recourse to environmental sampling, major remedial construction work or extensive molecular strain or plasmid typing.